The Application of the Principles of Logos, Ethos, and Pathos in the Context of Da'wah - Iim, Ade; Satriah, Lilis (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
This study aims to explore the application of rhetorical principles in preaching based on the teachings of the Qur'an and to provide practical guidance for preachers in improving the quality of their preaching messages. This study uses a qualitative approach with a literature review method, as the focus of the study is on understanding the application of rhetorical principles in the context of da'wah, which requires careful text analysis and theoretical interpretation. The analysis was conducted using an interpretive approach, in which the texts of the Qur'an and hadith were interpreted in the context of the aforementioned principles of rhetoric. This process involves identifying and interpreting relevant verses that demonstrate the application of the principles of logos, ethos, and pathos in da'wah. This study found that the principle of logos helps explain Islamic teachings in a logical and convincing manner. The credibility of a preacher, supported by deep knowledge, noble character, and active involvement in the community, increases the trust of the audience. Ethos builds a strong relationship between the preacher and the audience. Pathos helps touch the hearts of the audience and makes the message more impactful. The combination of logos, ethos, and pathos in preaching increases the effectiveness of message delivery.